Effect of Meridian Scraping Therapy Combined with Rehabilitation Training on sEMG and Dynamics of Upper Limb of Hemiplegic Stroke - Zhiqiang HUANG; Ning ZHAO; Zhaoyuan SU; Jiafu SU; Qiang WU (康复学报)
Objective:To investigate the effects of meridian scraping therapy combined with rehabilitation training on the dynamics and surface electromyography (sEMG) of the biceps brachii and triceps brachii muscle in hemiplegic stroke patients.Methods:A total of 80 patients with hemiplegic upper limb muscle tension after stroke were randomly assigned to the comprehensive therapy group and baclofen group, with 40 patients in each group. The baclofen group received baclofen tablets, and the comprehensive therapy group received both baclofen tablets and meridian scraping therapy on Yin and Yang channels of upper limb. Both groups also received same rehabilitation training once a day, five times each week for four weeks. The biceps and triceps sEMG values of IEMG in the ipsilateral elbow flexion and extension of the maximum isometric contraction were recorded, and the elbow flexion and extension moment and the corresponding co-contraction ratio were calculated before and after the treatment. Modified Ashworth scale, range of elbow joint motion and Fugl-Meyer assessment were applied to evaluate biceps brachii muscle tonus changes of spastic upper limb when the affected elbow flexion, range changes of elbow joint motion and recovery of motor function.Results:After the treatment, the elbow flexion and extension torque of both groups were higher than those before (P<0.05), and the co-contraction ratio was lower than that before (P<0.05). After the treatment, the increasing amplitude of affected elbow extension torque of comprehensive therapy group was higher than that of baclofen group, the decreasing amplitude of biceps brachii co-contraction ratio was higher than that of baclofen group (P<0.05). After the treatment, the spastic degree of affected biceps brachii muscle, elbow autonomic activity and upper limb motor function of both groups were improved (P<0.05), and the improvement of comprehensive therapy group was better than that of baclofen group (P<0.05).Conclusion:Meridian scraping therapy combined with rehabilitation training can strengthen the elbow extension strength of spastic upper limb of hemiplegic stroke patients, improve the coordination of elbow flexion and extension movement, reduce the affected biceps brachii tension, increase the affected elbow joint activity and improve the motor function of upper limbs.